The Relationship Between Knowledge and Attitudes Toward Mask Usage Compliance Among High School Students at State High School 3 Cibinong as a Prevention Measure Against COVID-19 - Exaudi Dita Eirene; Evi Maryam (International Journal Labs, 2025)
Corona Virus Disease 2019 spread rapidly throughout the world until WHO declared Covid-19 as a Public Health Emergency of International Concern (PHEIC) on January 30, 2020. Covid-19 can spread through droplets of respiratory secretions from people infected with Covid-19, and the droplets remain infectious when floating in the air. Therefore, the use of masks as one of the preventive measures against Covid-19 is very important. This research aimed to determine and understand the relationship between knowledge and attitudes toward compliance with the use of masks in SMA Negeri 3 Cibinong students for the prevention of Covid-19. This research was an analytical observational study with a cross-sectional research design and a sample of 168 people. Primary data collection was conducted using a questionnaire. Data processing was conducted using univariate, bivariate, and multivariate analysis with data analysis using the chi-square test. Data obtained from 147 students (87.5%) indicated high knowledge of mask use in preventing COVID-19, 148 students (88.1%) demonstrated an attitude supporting mask use in preventing COVID-19, and 122 students (72.6%) consistently used masks as a preventive measure against COVID-19. Statistically, there was a relationship between knowledge and adherence to the use of masks in the prevention of Covid-19 with a p-value of 0.001 and there was a relationship between attitudes toward compliance with the use of masks as prevention of Covid-19 with a p-value of 0.000. Attitude is the most influential variable in compliance with mask use for the prevention of Covid-19.